The Guarantees for Accused Persons Under the Article of the European Convention on Human Rights: An Analysis of the Application of the Convention and a Comparison with other Instruments - Butler, Andrew S (Victoria University of Wellington Law Review, 1996)
This article is a book review of Stephanos Stavros The Guarantees for Accused Persons under Article 6 of the European Convention on Human Rights: An Analysis of the Application of the Convention and a Comparison with Other Instruments (Martinus Nijhoff, Dordrecht, 1993) 388 pp (including 3 appendices), price (hbk) Â£87.00. This book is a detailed analysis of the case law of the organs of the European Convention on Human Rights on the interpretation and application of Article 6 of the Convention. That article guarantees fair trial rights in the determination of criminal charges and in the determination of civil rights and obligations. The scope of Dr Stavros' study is the rights of an accused under Article 6. Butler praises Dr Stavros for being thorough in his treatment of both case law and international law, providing a closely argued critique alongside the law presented, and for his general enthusiasm for the subject matter (reflected in the book's readability). Despite its limitations, Butler commends this book's high standard of scholarship overall.